Family Members' Experience With Hospice in Nursing Homes. (May 2016) - Gage, L. Ashley; Washington, Karla; Oliver, Debra Parker; Kruse, Robin; Lewis, Alexandra; Demiris, George
Research has documented numerous benefits and challenges associated with receipt of hospice care in nursing homes; however, study of this partnership from the perspective of residents' family members has been limited. The purpose of this qualitative investigation was to explore family members' experience with hospice services received in the nursing home setting. Researchers conducted a secondary data analysis of 175 family member interviews using a thematic analytic approach. Findings highlighted the critical role of communication in supporting residents and their family members. Care coordination, support and oversight, and role confusion also impacted family members' experience of hospice care in the nursing home. Efforts directed at enhancing communication and more clearly articulating the roles of members of the health care team are indicated.